Telemedicine for diabetic retinopathy screening using an ultra-widefield fundus camera - Hussain,Nazimul; Edraki,Maryam; Tahhan,Rima; Sanalkumar,Nishanth; Kenz,Sami; Khalil,Nagwa; Mtemererwa,Brian; Mohammed,Nahid (Clinical Ophthalmology, 2017)
Nazimul Hussain,1 Maryam Edraki,2 Rima Tahhan,2 Nishanth Sanalkumar,2 Sami Kenz,2 Nagwa Khalil Akasha,2 Brian Mtemererwa,2 Nahed Mohammed2 1Department of Ophthalmology, Al Zahra Hospital, Sharjah, United Arab Emirates; 2Department of Endocrinology, Al Zahra Hospital, Sharjah, United Arab Emirates Objective: Telemedicine reporting of diabetic retinopathy (DR) screening using ultra-widefield (UWF) fundus camera. Materials and methods: Cross-sectional study of diabetic patients who visited the endocrinology department of a private multi-specialty hospital in United Arab Emirates between April 2015 and January 2017 who underwent UWF fundus imaging. Fundus pictures are then accessed at the Retina Clinic in the Department of Ophthalmology. Primary outcome measure was incidence of any form of DR detected. The secondary outcome measure was failure to take good image and inability to grade. Results: A total of 1,024 diabetic individuals were screened for DR from April 2015 to January 2017 in the department of Endocrinology. Rate of DR was 9.27%; 165 eyes of 95 individuals were diagnosed to have some form of DR. Mild non-proliferative DR (NPDR) was seen in 114 of 165 eyes (69.09%), moderate NPDR in 32 eyes (19.39%), severe NPDR in six eyes (3.64%), and proliferative DR (PDR) in 13 eyes (7.88%). The secondary outcome measure of poor image acquisition was seen in one individual who had an image acquired in one eye that could not be graded due to bad picture quality. Conclusions: The present study has shown the effectiveness of DR screening using UWF fundus camera. It has shown the effectiveness of trained nursing personnel taking fundus images. This model can be replicated in any private multi-specialty hospital and reduce the burden of DR screening in the retina clinic and enhance early detection of treatable DR. Keywords: telemedicine, ultra-widefield camera, diabetic retinopathy screening